The Effect of Spectacle-Induced Low Myopia in the Non-Dominant Eye on the Binocular Defocus Curve with a Non-Diffractive Extended Vision Intraocular Lens - Gundersen KG (Dove Medical Press, 2021)
Kjell G Gundersen,1 Richard Potvin2 1IFocus Øyeklinikk AS, Haugesund, Norway; 2Science in Vision, Bend, OR, USACorrespondence: Kjell G Gundersen Email kg@ifocus.noPurpose: To quantify the changes in the binocular defocus curve associated with the Vivity™ non-diffractive extended vision intraocular lens when the dominant eye was targeted for emmetropia and the non-dominant eye was artificially targeted for slight myopia using spectacles.Patients and Methods: This was a non-interventional research study of the corrected binocular defocus curve associated with binocular emmetropia (Setting A) and with emmetropia in the dominant eye and two different levels of myopia simulated in the non-dominant eye (− 0.50 D, Setting B and − 1.00 D, Setting C). Subjects were patients implanted with the AcrySof® IQ Vivity® intraocular lens in both eyes 3 to 12 months previously. Using the defocus data, the percentage of subjects with a continuous 2.5 D range of vision (distance to 40 cm) was calculated for various levels of minimum visual acuity (VA).Results: Forty subjects were enrolled. The mean spherical equivalent refraction was − 0.06 D ± 0.36 D, with 0.37 D ± 0.29 D of refractive cylinder. There was no statistically significant difference in the mean VA at − 0.25 D or at − 0.50 D vergences between the test Settings, but there was a statistically significant difference at all other vergences. Differences were particularly noticeable at − 2.00 D, − 2.50 D and − 3.00 D, where higher myopia in the non-dominant eye yielded better binocular VA. A 2.5 D range of functional vision (20/25) was achieved by 38% of subjects at Setting A, 68% of subjects at Setting B and 85% of subjects at Setting C. At setting C, all but one subject (39/40, 97.5%) had a 2.5 D range of vision with a VA of 20/32 or better.Conclusion: Significant gains in binocular near vision, with only a nominal effect on distance vision, can be achieved with the Vivity IOL by leaving the non-dominant eye of patients with 0.50 D or 1.00 D of myopia.Keywords: non-diffractive, extended vision, extended depth of focus, presbyopia, cataract